Effect of isothermal aging and copper substrate roughness on the SAC305 solder joint intermetallic layer growth of high temperature storage (HTS) - Rabiah Al Adawiyah Ab Rahim; Muhammad Nubli Zulkifli; Azman Jalar; Atiqah Mohd Afdzaluddin; Kim, Siow Shyong (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study aims to evaluate the effect of copper (Cu) substrate surface roughness on the intermetallic compound (IMC) growth and interfacial reaction of SAC305 lead-free solder joint after undergone an aging process. Aging process was conducted using high temperature storage (HTS) at temperature of 150 °C and aging times of 200, 400, 600, 800, and 1000 h. IMC morphology and growth were examined using infinite focus microscope (IFM). Then, the SAC305 solder joint IMC growth kinetic was measured based on power law relationship and diffusion coefficient formula. It was noted that the morphology of IMC for the rougher Cu substrate has scallop-shaped and uniform layer as compared to that of smoother Cu substrate for the initial exposure to the HTS. In addition, Cu substrate with Ra of 579 nm is the turning point for the creation of Cu6 Sn5 towards more Cu3 Sn of IMC. In addition, Cu substrate with Ra of 579 nm also acts as the turning point for the IMC growth of SAC305 solder joint on Cu substrate for the solid-state diffusion to be happened during 150 °C of aging from grain boundary dominant toward volume diffusion dominant.